The development of a three-dimensional model of the ice growth process on aerodynamic surfaces - Alekseyenko, Sergey; Yushkevich, Оleg (Technology audit and production reserves, 2019)
The object of research is the processes of hydroaerodynamics and heat and mass transfer that occur when icing the aerodynamic surfaces of aircraft during flight in adverse weather conditions. One of the problem areas in the development of software and methodological support that allows to simulate the icing processes, there are difficulties in the transition to solving the problem in three-dimensional formulation. As well as the presence of contradictions in existing methods in describing the physical picture and, accordingly, the thermodynamics of the process of ice growth. During the study, experimental and analytical methods were used to study the physical processes of ice growth on streamlined surfaces, based on a phased analysis of the interaction of supercooled droplets with the surface and their subsequent freezing at the wing edge. The proposed model of the process of ice growth is based on the use of the method of surface control volumes, based on the equations of continuity, conservation of momentum and energy. Based on the new experimental data obtained on the physics of icing, it is proposed to separate the processes of the formation of a bulk ice-water structure and subsequent complete freezing of this structure separately in the methodology for modeling ice growth. At the first stage of the fluid crystallization process, as part of the step on the icing time, the supercooled fluid contained in the droplets that fall on the streamlined surface passes into a state of thermodynamic equilibrium. That is, the latent heat of solidification released during the formation of an ice fraction in the ice-water structure will be equal to the internal heat required to heat the supercooled fluid from the temperature of the droplets to the temperature of the phase transition. At the second stage, the water contained in the ice-water structure will freeze due to heat loss by convection, evaporation, sublimation, thermal conductivity (minus the latent heat of solidification, kinetic and aerodynamic heating). It should be noted that the water that will freeze will also fetter the spatial ice structure. In this case, the method of successive approximations is applied to determine the direction of fluid movement along the streamlined surface. Compared with the well-known traditional methods, this approach makes it possible to take into account to a greater extent the real physical processes of icing of aerodynamic surfaces that are extremely complex for mathematical description. The results can be used to optimize the operation of anti-icing systems and determine ways to reduce energy costs during the operation of such systems.